Optimization of a protease extraction using a statistical approach for the production of an alternative meat tenderizer from Spondias cytherea roots - Ahmad, Mohammad Norazmi; Mat Noh, Nor Aini; Abdullah, Erna Normaya; Yarmo, Mohd Ambar; Mat Piah, Mohd Bijarimi; Ku Bulat, Ku Halim (Wiley, 2019)
Abstract In this research, a novel protease from Ambarella (Spondias cytherea) was identified as a new potential halal meat tenderizer. Optimization of protease extraction by response surface methodology has found the optimized variables at pH 8.22, 4.95% of TX‐100, 6.80 mM of 2‐mercaptoethanol, and 1.71 min of mixing time at 12.37 U/g of protease activity. The overall model was significant (p < .05) with an R2 value of 0.9885. Verification test results (Tukey's test) showed that no significant difference between the expected and experimental protease activity value (98%). The enzyme was stable at pH 8.0–10.0 and temperature 50–60°C. Incubation of enzyme with organic solvents showed higher activity in hydrophobic than hydrophilic phases. In addition, prolonged storage time of enzyme decreased the activity by 32%. Protein bands of muscle proteins and firmness of muscle samples were reduced upon protease treatment due to breaking of tissue fibers and loosening of myofibrils. Practical applications Treatment by exogenous proteases is one of the various tenderization techniques used in the meat industry to improve meat tenderness. Myofibrillar and connective tissue proteins which cause toughness in meat were effectively hydrolyzed by the protease enzymes. The results of the present study should be useful to the meat industry for discovering new source of plant protease which is able to overcome the shortcoming of animal and microbial proteases as meat tenderizer.